Mixed-methods evaluation of a Global South-North research fellowship in Uganda: Global health experiential fellowship (GHEF) - Yang Jae Lee; Rauben Kazungu; Ibrahim Ssekalo; Scott Blackwell; Kayera Sumaya Nakaziba; Emery Monnig; Rita Mbabazi; Peter Muwereza; Faizo Waiswa; Haba Ingabire; Alesha Cid Vega; Adam D. Brown; et al. (SSM - Mental Health, 2025)
Introduction: Integrated, simultaneous training of Global South and North trainees offers novel opportunities to enhance equitable collaboration and research capacity in global health. While existing programs often focus on exchange rotations or separate training tracks, simultaneous training of Global South and North trainees in the same intensive program remains understudied. We describe the Global Health Experiential Fellowship (GHEF), which combines research training with shared living arrangements and collaborative work in rural Uganda. Program description: GHEF is a five-week research training program for pre-doctoral students from Uganda and the United States. The program addresses power imbalances in North-South partnerships through shared leadership between Ugandan and American co-directors, with Ugandan team leaders supervising daily activities. Fellows work in mixed teams on qualitative mental health projects, while shared living arrangements foster cultural exchange. Since 2021, GHEF has trained 39 Ugandan students from three universities and 102 American students from 12 universities. Ugandan fellows participate without fees, subsidized by American fellows. Methods: We conducted a mixed-methods evaluation. Qualitative data were collected through interviews with 10 fellows (5 Ugandan, 5 American). Research skills were assessed using the Assessment of Key Interviewing Factors for Research Assistants (AKIRA) pre- and post-fellowship among 14 fellows (7 Ugandan, 7 American). Results: Ugandan fellows gained formal research training, while American fellows gained perspectives on field-based methodologies. Cultural exchange facilitated intercultural learning. AKIRA scores showed improvement in Ugandan fellows’ skills (pre-fellowship mean = 1.125; post-fellowship mean = 1.536; p = 0.0117). Discussion: GHEF's simultaneous training model offers a promising approach to equitable collaboration and building research capacity in global mental health.